Comparison of the effects of local anesthesia and epidural anesthesia for percutaneous transforaminal endoscopic discectomy in elderly patients over 65 years old. (December 2017) - Zhu, Yanjie; Zhao, Yongzhao; Fan, Guoxin; Gu, Guangfei; Sun, Shiyu; Hu, Shuo; He, Shisheng
Abstract: Background: Local anesthesia (LA) is recommended for percutaneous transforaminal endoscopic discectomy (PTED) but clinical practice indicates that LA cannot achieve satisfactory pain management during PTED. Objectives: The study aimed to investigate the comparisons between LA and EA for PTED in elderly population over 65 years old. Methods: We performed a retrospective analysis of patients over 65 years old received PTED from May 2013 to December 2014. And patients were divided into two groups according to the anesthesia method. The data collected for analysis including operative time, fluoroscopy time, postoperative bed time, visual analog scale (VAS), Oswestry Back Pain Disability Index (ODI), the global outcome based on the Macnab outcome criteria, satisfaction rate of anesthesia, and complications. Results: A total of 132 consecutive patients were enrolled in this study. There were 65 patients in LA group and 67 patients in EA group. Compared to LA group, EA group had longer operative time (P < 0.001) and postoperative bed time (P < 0.001) but shorter fluoroscopy time, (P < 0.001), smaller VAS score of lumbar pain intraoperatively (P < 0.001), 1-h postoperatively (P < 0.001) and 1-week postoperatively (P < 0.001). Similarly, EA group had lower VAS score of leg pain intraoperatively (P < 0.001) and 1-h postoperatively (P < 0.001). In additions, higher satisfaction rate of anesthesia was observed in EA group (P = 0.029). Conclusions: EA and LA for PTED achieved comparable clinical outcomes in elderly population over 65 years old. However, compared to LA for PTED, EA had a better performance in pain management. Highlights: The first study to compare the effects of local anesthesia and epidural anesthesia for percutaneous transforaminal endoscopic discectomy in elderly patients over 65 years old.